ELECTRICAL CONDUCTIVITY AS AM~A~URE OF PLANTING SE~D QUALITY IN COTTON (Biological Sciences - PJSIR, 2022)
Investigations were conducted to relate seed exudates conductance to standard germination so as to develop aquick and reliable test for measurement of cotton seed quality. Results showed thatcott. \11 cultiv ars differed significantlyin germination percentage and electrical conductivity. Cultivars MNH-93 and C!ivt-l09 had higher germinationpercentage and less exudate conductance compared to othcr cultivars. Seeds obtained from first pick were of poor qualitythan those of second pick. The exudate conductance was negatively correlated with germination (r = - 0.88**). The lossof membrane functional integrity sel~IIISresponsible lor lower germination. These data indicate that electricalconductivity test can provide estimates of seed quality,